The rise of buy-now-pay-later (BNPL) service in Malaysia - Chuah, Shian Huey; Koh, Jih Cheng; Puah, Irene Zheng Ying; Liew, Ka Seng; Liu, Yuan Kai (2023)
This study is aimed to find out the factors that affect the intention to adopt the Buy Now Pay Later (BNPL) Services in Malaysia. This study is using five factors (perceived ease of use, perceived usefulness, perceived risk, social influence, and financial literacy) to examine their significance to the intention to adopt BNPL in Malaysia by referring to TAM and UTAUT theory. We selected Malaysian citizens who were at the age above 18 years old, including users and non-users of BNPL as our target population. Our study collected 401 responses across Malaysia through online Google Forms and physical distribution of questionnaires. SPSS software is applied to examine the reliability and accuracy of data as well as find out the relationship between the dependent variable and independent variables. There are also various types of analyses, including the Pilot test, Cronbach’s Alpha, Pearson Correlation Analysis, and Multiple Regression Analysis are conducted in this study. The result analysis showed that perceived ease of use, perceived usefulness, social influence, and financial literacy have a positive relationship with the intention to adopt BNPL services in Malaysia. However, perceived risk has no significant relationship with the intention to adopt BNPL. Lastly, the study also figured out implications, limitations, and recommendations as references for regulators, researchers, and developers to help them sort out the current situation of BNPL services in Malaysia and the consumer behavior toward BNPL.